2011
DOI: 10.1007/s00406-011-0250-2
|View full text |Cite
|
Sign up to set email alerts
|

Subtle deficits of cognitive theory of mind in unaffected first-degree relatives of schizophrenia patients

Abstract: Alterations of theory of mind (ToM) and empathy were implicated in the formation of psychotic experiences, and deficits in psychosocial functioning of schizophrenia patients. Inspired by concepts of neurocognitive endophenotypes, the existence of a distinct, potentially neurobiologically based social-cognitive vulnerability marker for schizophrenia is a matter of ongoing debate. The fact that previous research on social-cognitive deficits in individuals at risk yielded contradictory results may partly be due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 81 publications
4
45
2
2
Order By: Relevance
“…However, some research indicates that reading fiction is associated with increased empathy and prosocial behavior (Johnson, 2012). In addition, given some literature linking fantasy abilities to increased psychotic symptoms (Sparks et al, 2010) and psychosis risk (Montag et al, 2012b), future research may try to glean a better understanding of how fantasy abilities affect (or are affected by) illness course and symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some research indicates that reading fiction is associated with increased empathy and prosocial behavior (Johnson, 2012). In addition, given some literature linking fantasy abilities to increased psychotic symptoms (Sparks et al, 2010) and psychosis risk (Montag et al, 2012b), future research may try to glean a better understanding of how fantasy abilities affect (or are affected by) illness course and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There is less evidence linking abilities to relate to fantasy characters to empathic or functional outcomes, but some literature shows a significant association between greater fantasy abilities and increased hallucinations and delusions (Sparks et al, 2010), and heightened fantasy abilities in relatives of people with schizophrenia have been associated with measures of psychosis risk (Montag et al, 2012b). Further, although no research to our knowledge has investigated this, it seems plausible that deficits in the ability to relate to fantasy characters may add another layer of difficulty to interpersonal interaction, where conversations may center on popular television shows or movies.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other studies have found genetic liability effects in first-degree relatives [84][85][86][87][88]. Montag and colleagues reported impairments in ToM reasoning in parents and siblings of schizophrenic patients (not explained by other aspects of neurocognitive measures) using the 'Movie for the Assessment of Social Cognition' video-based task [87]. de Achával and colleagues [89] found that unaffected first-degree relatives showed underperformance on the Faces Test, Reading the Mind in the Eyes Test and the detection of social Faux Pas.…”
Section: First-degree Relatives Of Schizophreniamentioning
confidence: 64%
“…A study by Anselmetti et al [83] assessed relatives of schizophrenia patients and healthy controls using the ToM picture sequencing task, and reported ToM deficits in parents (separate score for mother and father) of patients with schizophrenia. Similarly, other studies have found genetic liability effects in first-degree relatives [84][85][86][87][88]. Montag and colleagues reported impairments in ToM reasoning in parents and siblings of schizophrenic patients (not explained by other aspects of neurocognitive measures) using the 'Movie for the Assessment of Social Cognition' video-based task [87].…”
Section: First-degree Relatives Of Schizophreniamentioning
confidence: 83%
“…39 Hence, new signal processing methods like single-trial classification and modeling of event-related brain dynamics using time-frequency or blind source separation analysis may be favorable for modeling complex pathophysiological network processes. [39][40][41] Next, new paradigms or the investigation of other cognitive domains, eg, theory of mind 42 or emotion recognition, 43 could prove highly beneficial for discriminating schizophrenia and control groups. Last, magnetic resonance imaging methods have shown to hold some promise for differentiating between schizophrenia and mentally healthy subjects.…”
Section: Discussionmentioning
confidence: 99%